Survival rate of oral squamous cell carcinoma patients treated for the first time in cancer centers between 2000 and 2011, Medellín-Colombia - Posada-López, Adriana; Palacio, Marta Aída; Salas-Z., Carolina; Álvarez-M., Efraín; Grisales, Hugo (Revista Facultad de Odontología Universidad de Antioquia, 2016)
Introduction: the goal of this study is to determine the survival rate of oral patients white oral squamous cell carcinoma (OSCC) who were treated for the first time in 9 cancer centers over a period of 12 years. Methods: analysis of survival rate based on a retrospective sample of 630 cases of oral squamous cell carcinoma (OSCC), according to individual and clinical variables. Relevant life tables were created in order to identify some of the characteristics related to patient survival time; the Kaplan-Meier method, the log Rank test, and the Cox proportional hazards model were used to assess survival ignificance in relation to relevant variables. Results: average patient age at the time of diagnosis was 63.5 years (SD = 13.6 years). 28.1% (177) of them died as a direct consequence of oral cancer, according to death certificates filled out by doctors on duty. Median survival rate was 6.1 years, and when discriminated by sex, age groups, and stage of disease, the median was higher in women, in patients under 50 years of age, and in those who were diagnosed with OSCC in stage I and received surgery as single treatment. Conclusions: the survival rate of OSCC patients who were treated for the first time in nine cancer centers of the city of Medellín in a 12-year period was 6.1 years. The authors recommend implementing a surveillance program allowing early diagnosis in order to decrease the sequelae and mortality from this disease.